Emerging role of neutrophil extracellular traps in the complications of diabetes mellitus - Shafqat, Areez; Abdul Rab, Saleha; Ammar, Osama; Al Salameh, Sulaiman; Alkhudairi, Anas; Kashir, Junaid; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Medicine, 2022)
Immune dysfunction is widely regarded as one of the central tenants underpinning the pathophysiology of diabetes mellitus (DM) and its complications. When discussing immunity, the role of neutrophils must be accounted for: neutrophils are the most abundant of the circulating immune cells and are the first to be recruited to sites of inflammation, where they contribute to host defense via phagocytosis, degranulation, and extrusion of neutrophil extracellular traps (NETs). NETs are composed of DNA associated with nuclear and cytosolic neutrophil proteins. Although originally reported as an antimicrobial strategy to prevent microbial dissemination, a growing body of evidence has implicated NETs in the pathophysiology of various autoimmune and metabolic disorders. In these disorders, NETs propagate a pathologic inflammatory response with consequent tissue injury and thrombosis. Many diabetic complications – such as stroke, retinopathy, impaired wound healing, and coronary artery disease – involve these mechanisms. Therefore, in this review, we discuss laboratory and clinical data informing our understanding of the role of NETs in the development of these complications. NET markers, including myeloperoxidase, citrullinated histone H3, neutrophil elastase, and cell-free double-stranded DNA, can easily be measured in serum or be detected via immunohistochemical/immunocytochemical staining of tissue specimens. Therefore, NET constituents potentially constitute reliable biomarkers for use in the management of diabetic patients. However, no NET-targeting drug is currently approved for the treatment of diabetic complications; a candidate drug will require the outcomes of well-designed, robust clinical trials assessing whether NET inhibition can benefit patients in terms of morbidity, quality of life, health expenditures, and mortality. Therefore, much work remains to be done in translating these encouraging pieces of data into clinical trials for NET-targeting medications to be used in the clinic.